Tribological Analysis of Thermal Spray Coatings of Ni and Al2O3 with Dispersion of Solid Lubricants in Erosive Wear Modes. (2016) - Tiwari, Sudhir; Christy, John V.
Abstract: Thermal spray coating was found very stable even in erosion, abrasion, scratch and heavy load conditions. At elevated temperatures, it protects the solid lubricants entrapped in it and thus causes the layer to be stable and dynamic. In the present work, Ni and 60% wt. of Al2 O3, were mixed in fixed proportion as thermal spray with entrapped solid lubricant through D–Gun on the substrate. The solid lubricants mixed in thermal spray were graphite and PTFE. The specimen was taken and cleaned properly and coated with thermal spray and solid lubricating coatings of 0.5 micrometer. These were then ultrasonically cleaned in the acetone bath. The coating is done by a duo spray pump that spurts the coating on the work piece. This pump spurting is controlled by a semi permeable membrane coated on the work piece. The coatings were evaluated for erosive wear performance. Coatings were tested at different air pressure, temperature and impingement angle. The Graphite and NiAl2 O3 coating is found to be more stable tribologically as compared to PTFE and NiAl2 O3 coating at high temperatures and pressures. Morphological analysis of coatings was also done.